2000
DOI: 10.1007/s002610000046
|View full text |Cite
|
Sign up to set email alerts
|

Transjugular retrograde obliteration for chronic portosystemic encephalopathy

Abstract: Chronic portosystemic encephalopathy (CPSE) is uncommon, and its management has yet to be determined. We have been able to control five cases of CPSE using transjugular retrograde obliteration (TJO), and we report our clinical results with this technique. All of the five patients were suffering from cirrhosis and had gastric varices and large gastrorenal shunts. According to Sherlock's classification, the grade of encephalopathy was II in two patients, III in two, and IV in one. According to Child's classifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…38,[45][46][47] It has also been considered that B-RTO could be a useful therapy for chronic hepatic encephalopathy. However, the NH 3 level was not changed significantly in the present study, and it is considered that this may have been due to some portosystemic shunt other than a gastrorenal shunt.…”
Section: Discussionmentioning
confidence: 99%
“…38,[45][46][47] It has also been considered that B-RTO could be a useful therapy for chronic hepatic encephalopathy. However, the NH 3 level was not changed significantly in the present study, and it is considered that this may have been due to some portosystemic shunt other than a gastrorenal shunt.…”
Section: Discussionmentioning
confidence: 99%
“…Methods of shunt occlusion include surgical treatment and interventional radiology (IVR). When based on the direction of blood flow, IVR can be classified into two types, one including B-RTO (9-11) and transjugular retrograde obliteration for gastric varices (21,22), which are retrograde embolizations, and the other including transileocolic venous obliteration (23) and PTO (6), which are antegrade embolizations.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have reported the safety and efficacy of transcatheter embolization of portosystemic shunts in patients with refractory HE [13,[32][33][34][35][36][37][38]. In addition, in the previous 10 years, many case reports on HE due to portosystemic shunts that were successfully treated by transcatheter embolization have been published [17][18][19][20][21][22][23][39][40][41][42].…”
Section: Efficacy and Safety Of Transcatheter Embolizationmentioning
confidence: 99%
“…The details and outcomes of the reviewed studies are listed in Table 1 [13,[32][33][34][35][36][37][38].…”
Section: Efficacy and Safety Of Transcatheter Embolizationmentioning
confidence: 99%